Science and technology policies and structures in Southern Africa : a discussion of the concept of national system of innovation with reference to Malawi, Namibia and South Africa - Maluke, Rethabile Olive (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2004.